Arat Sabulungan as A Sacred Ecology: Sustainable Consumption and Climate Change Adaptation Among the Mentawai Tribe - Islami, Moch Zihad; Nisa, Aza Khiatun; Fitri, Nur Amalia; Wajdi, Muhammad Farid; Situmorang, Kartika; Sartini, Sartini; Selamat, Iffah Liyana Binti (Lembaga penelitian dan pengabdian kepada Masyarakat, 2023)
Climate change and consumption of sustainable resources are global issues internalized in the Sustainable Development Goals (SDGs). In fact, local wisdom has accommodated the concept of sustainable development. However, local wisdom is currently less involved in the SDGs. This research seeks to ensure that local wisdom, including the Mentawai Arat Sabulungan (AS), can support SDGs 12 and 13 in Indonesia. The purpose of this research is to explore the position and role of the AS, to analyze the correlation between the AS and the SDGs mission to address climate change and sustainable resource consumption, and to formulate efforts to implement national SDGs points 12 and 13 through a cultural approach. The research method used is qualitative research by collecting data through interviews, observation, and literature studies. The results of this study are: First, AS is the belief system of the Mentawai people as an ecological awareness that is based on sacred values and functions as a religious principle, social norm, and environmental conservation. Second, the AS concept of sacred ecology has relevance to the SDGs on sustainable consumption and efforts to deal with climate change. Third, the strategy for implementing SDGs points 12 and 13 can be carried out by localizing it.